The effect of eight weeks of high-intensity interval swimming training on the expression of liver RBP4 protein, serum hs-CRP and insulin resistance in rats with Non-Alcoholic Steatohepatitis caused by consumption of high-fat diet - Mohammad Amin Delavari; Elham Shahabpour; Alireza Jowhari (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: Nonalcoholic steatohepatitis (NASH) is an important public health problem, and Retinol-Binding Protein 4 (RBP4) is closely related to this disease. RBP4 is the only known specific transporter protein for vitamin A that regulates circulating levels of retinol as an antioxidant. Liver tissue is the main producer of RBP4 and can contribute to whole body retinoid homeostasis. The accumulation of triglycerides leads to an increase in the level of inflammation and oxidative stress, and in response to this change, the level of RBP4 and inflammatory markers such as high-sensitivity C-reactive protein (hs-CRP) may change. Thus, it is possible that with the progress of the disease and the increase in the level of oxidative stress and inflammation, the markers that respond to them, including RBP4 and hs-CRP, will also change. Therefore, the aim of this study was to investigate the effect of eight weeks of high-intensity interval swimming training on liver RBP4 protein expression, serum CRP and insulin resistance level in rats suffering from non-alcoholic steatohepatitis caused by consumption of high-fat diet.Materials and Methods: Forty male Sprague-Dawley rats (Mean±SD; age, 6 to 8 weeks; weight 230±20 grams) were divided into four groups of control-NASH (n=9), exercise-NASH (n=9), control-healthy (9 = n) and exercise-healthy (n = 9). HIIT swimming included 20 repetitions of 30 s swimming with 30 s rest between repetitions (eight weeks, three days a week, on the even days). After the training period, intrahepatic RBP4 protein was measured by western blot technique and hs-CRP, insulin and fasting blood sugar were measured by ELISA and photometric methods. One-way ANOVA test was used to determine between-group differences and Bonferroni's post-hoc test was used to identify which mean differences were statistically significant.Results: There was a significant increase of RBP4 in the control-NASH group compared to the healthy control (P=0.004) and a non-significant decrease in RBP4 (P=0.762) and insulin resistance (P=0.14) in exercise-NASH compared to the control-NASH. Furthermore, significant decreases in hs-CRP (P=0.007) and fasting blood sugar (P=0.001) were observed in the exercise-NASH group compared to the control-NASH.Conclusion: Interval high-intensity swimming training can reduce systemic inflammation in non-alcoholic steatohepatitis. Therefore, it seems that this new type of exercise can prevent the progression of this disease through the control of intrahepatic RBP4 protein and insulin resistance. Therefore, this type of exercise protocol can be useful in improving NASH, though, more research is needed in this field to fully prove it.